ON THE QUESTION OF THE WAVE NATURE INNOVATION PROCESSES IN THE ECONOMY - Aleksandr A. Fomin (Статистика и экономика)
The methodological and methodical basesof research of economic crises are stated the article. The main attention is paid to the cyclical nature of crises. The reasons that unbalance the world economy andlead to economic crises in the world and in Russia are explored. The relationship of the wave nature of the world economywith the cyclical nature of technologicaldevelopment are considered. The wayout of the economic crisis in Russia and a new systematic approach to transition toan innovative model of Russian economyare provided.